2006
DOI: 10.1080/10428190500513827
|View full text |Cite
|
Sign up to set email alerts
|

Adverse prognostic impact ofCDKN2Bhyper-methylationin acute promyelocytic leukemia

Abstract: The use of all-trans retinoic acid (ATRA) has markedly improved the survival of patients with acute promyelocytic leukemia (APL), making it potentially curable. However, the identification of prognostic markers predictive of durable remission remains an important aspect in risk-adjusted treatment algorithms. High presentation leucocyte count has been found to correlate with inferior disease-free-survival (DFS). However, recent studies have also shown aberrant promoter methylation of the CDKN2B (alias p15) gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 65 publications
1
4
0
Order By: Relevance
“…This can also occur in primary leukemic blasts isolated from patients with myelodysplastic syndrome (MDS) and AML [24], and hypermethylation of the p15 INK4B promoter is associated with a poor prognosis in MDS and AML [24], [25], [26]. Our previous computer modeling and enzymatic study demonstrated that curcumin is capable of blocking DNMT1 enzymatic activity [19], and here we have shown that curcumin can also down-regulate DNMT1 gene expression.…”
Section: Resultssupporting
confidence: 51%
“…This can also occur in primary leukemic blasts isolated from patients with myelodysplastic syndrome (MDS) and AML [24], and hypermethylation of the p15 INK4B promoter is associated with a poor prognosis in MDS and AML [24], [25], [26]. Our previous computer modeling and enzymatic study demonstrated that curcumin is capable of blocking DNMT1 enzymatic activity [19], and here we have shown that curcumin can also down-regulate DNMT1 gene expression.…”
Section: Resultssupporting
confidence: 51%
“…Additionally, some of these genes are targets of cancer treatments. While GADD45A expression has been associated with the efficiency of 5-aza-CdR to treat different pancreatic cancer cell lines [23], CDKN2B, a cyclin-dependent kinase inhibitor, is a tumor suppressor gene that inhibits cell cycle progression [24]. Interestingly, SERTAD1, which is known to inhibit p16 INK4a activity [25], is overexpressed in several cancers and associated with oncogenic potential [26].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, unlike the association of TSG with clinical parameters, such as the association of CDKN2B and WIF1 methylation with high presenting leukocyte count in acute promyelocytic leukemia [ 32 , 33 ], methylation of these miRs did not correlate with demographic, presenting blood counts, JAK2 V617F mutation or complications including thrombosis and myeloid transformations.…”
Section: Discussionmentioning
confidence: 99%